Plethysmographic and anthropometric validation of a 3D body image digitizer to determine body dimensions - Ramos-Jimenez, Arnulfo (2018)
Image digitizing has facilitated body shape evaluation gained entry in ergonomics industry, in fashion and in health. Objective: to validate the 3D image digitizer (TC2-18) to determine body dimensions in a fast and reliable manner. Methods: 285 adults of both sexes were studied to measure anthropometrics, plethysmography, and digitized body shape. Results: Digitizer obtained measurements highly correlated with those obtained through anthropometrics and plethysmography (R2 ≥ 0.75). However, the TC2-18 gave lower values in total body volume when compared with plethysmography (CI 95%, −3.9 to −3.5 L). In contrast, the TC2-18 yielded higher values in mesosternal (CI 95%, 8.8–9.6 cm), neck (CI 95%, 2.6–3.0 cm), gluteus maximus (CI 95%, 3.1–3.7 cm), relaxed arm (CI 95%, 2.9–3.3 cm), and minimal waist (CI 95%, 3.1–3.7 cm) circumferences; as well as similar data for the upper thigh, calf and forearm circumference. Conclusion: TC2-18 3D digitizer yielded valid and reliable measures when adult persons are evaluated. Found differences occur due to movement during digitizing and by difference inherent to the used devices.